Administration of estates in Malaysia: law and procedurels. 2nd ed. - Halim, Akmal Hidayah (Thompson Reuters Malaysia Sdn Bhd (Sweet & Maxwell Asia), 2018)
Administration of Estates in Malaysia: Law and Procedure (2nd Edition) is an updated and highly readable book designed to provide an overview of the theoretical and procedural framework relating to estates administration for both Muslims and non-Muslims in Malaysia. This book focuses on the jurisdictions, scopes and procedures for estates administration by the High Court, Estates Distribution Division, Corporation (Amanah Raya Berhad) and Syariah Court, being the administrative bodies responsible for estates administration in West Malaysia. The discussion also includes the administration of estate in Sabah and Sarawak. The procedures are visualized in form of charts to illustrate the process flow of the administration process and sample forms are provided to serve as quick references to the process.